Advanced environmental monitoring with remote sensing time series data and R - Gemitzi, Alexandra; Koutsias, Nikolaos; Lakshmi, Venkataraman, 1966- (Boca Raton : CRC Press, 2020)
'Provides a step-by-step guide on how to use various publicly-available, remotely-sensed time series data sources for environmental monitoring and assessment. Readers will learn how extract valuable information on global changes from a 20-year collection of ready-to-use remotely-sensed data through the free, open GIS and statistical software R. The case studies are from the Mediterranean region- a designated hot spot regarding climate change effects. Each chapter is dedicated to specific remote sensing products chosen for their spatial resolution. The methods used are adapted from large-scale to smaller-scale problems for different land cover areas'--
Environmental application of medium to high resolution remotely sensed data -- Environmental applications of medium resolution remote sensing imaging -- Environmental applications of low resolution remotely sensed data -- Processing remotely sensed data.
Includes bibliographical references and index.
Keywords: Environmental monitoring -- Remote sensing; Remote sensing -- Data processing; Time-series analysis -- Data processing; R (Computer program language); Environmental monitoring -- Mediterranean Region -- Remote sensing -- Case studies